FLUID: Improving Throughputs in Enterprise Wireless LANs through Flexible Channelization - Rayanchu, Shravan; Shrivastava, Vivek; Banerjee, Suman; Chandra, Ranveer (ACM MobiCom (top 3 papers fast tracked to IEEE Transactions of Mobile Computing), 2011)
This paper introduces models and a system for designing 802.11 wireless LANs (WLANs) using flexible channelization — the choice of an appropriate channel width and center frequency for each transmission. In contrast to current 802.11 systems that use fixed width channels, the proposed system, FLUID, configures all access points and their clients using flexible channels. We show that a key challenge in designing such a system stems from managing the effects of interference due to multiple transmitters employing variable channel widths, in a network-wide setting. We implemented FLUID in an enterprise-like setup using a 50 node testbed (with off-the shelf wireless cards) and we show that FLUID improves the average throughput by 59% across all PHY rates, compared to existing fixed-width approaches.